90Y-DOTA-CHS Microspheres for Live Radiomicrosphere Therapy: Preliminary In Vivo Lung Radiochemical Stability Studies. (3rd February 2014) - Amor-Coarasa, Alejandro; Milera, Andrew; Carvajal, Denny; Gulec, Seza; McGoron, Anthony J.
Abstract : Chitosan (CHS) is used to prepare microspheres of 31 ± 8 µ m size. Surface modification with p-SCN-Bn-DOTA was performed. A maximum 90 Y capacity was found to be 12.1 ± 4.4 µ Ci/particle. The best obtained labeling yield was 87.7 ± 0.6%. More than 90% in vitro stability was found. Particle in vitro degradation half-life in PBS was found to be greater than 21 days. In vivo studies with 90 Y-DOTA-CHS showed more than 95% of the injected activity (decay corrected) in the lungs 24 hours after tail vein administration. 90 Y-DOTA-CHS in vivo label stability was superior to resin microspheres. The addition of p-SCN-Bn-DOTA served as a radioprotectant for bone marrow as the 5% 90 Y released, during the first 24 hours, was quickly eliminated via urine.